The complete mitochondrial genome of a rare human pathogen, Aspergillus ustus. (1st November 2016) - Ruan, Zhi; Dai, Fangwei; Fang, Xu; Chen, Huan; Yu, Dongliang
Abstract: Aspergillus ustus is among the most ubiquitous soil species and has been implicated in human infections. The complete mitochondrial genome of A. ustus has been determined by high-throughput sequencing technology in this work. Our study revealed that the mitochondrial genome of A. ustus is 33, 007 bp long, with AT content of 74.84%, which consists of a usual set of mitochondrial proteins and RNA genes, including large and small ribosomal RNAs, 15 proteins and 20 tRNA genes and contains two introns. Notably, it also contains three hypothetical proteins without obvious homology to any known proteins. All structural genes are located on one strand and are apparently transcribed in one direction. The complete mitochondrial genomes of A. ustus would be useful for future investigation of the genetics, evolution and clinical identification of Aspergillus species.